Smoking Family Members In The House As Factor Risk Of Pneumonia Events In Children In Puskesmas Papanggo North Jakarta, In 2019 - Hasbye Hasadiki, Muhammad (Journal of Ageing And Family, 2021)
The incidence of pneumonia in children under five in the district health center in Papuan, North Jakarta, has increased from 2017-2018 to 156 cases. The purpose of this study was to study and explain smoking as a factor in the incidence of pneumonia in infants. This research is a quantitative study using case control design. The sample consisted of 204 respondents consisting of 68 cases namely toddlers with pneumonia and 136 controls without pneumonia. Analysis of the data used is, univariate, bivariate, chi square, and multivariate using multiple logistic regression. The results of this study showed that most of the toddlers are <12 months of age by 35.3%, male sex 51.5%, underweight nutritional status by 85.3%, toddlers with BLB <2500 grams by 20.6% , exclusive breastfeeding was not given for 22.1%, measles immunization was never 27.9%, incomplete DPT immunization was 5.9%, maternal knowledge was less than 79.4%, maternal education was low by 57.4%, mothers work by 16.2%, Density of occupancy is not standard 42.6%, have used mosquito repellent 67.6%, there are family members smoking 61.8%, there is a history of asthma of 64.7%, who do not use health insurance by 33.8%. Keywords:, smoking family members, toddlers, factors of incidence of pneumonia,